2002
DOI: 10.1046/j.1444-2906.2002.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the end-point temperature of heated fish and shellfish meats

Abstract: Attempts have been made to assess the end‐point temperature (EPT) of heated fish and shellfish meats by using the coagulation method together with sodium dodecylsulfate polyacrylamide gel electrophoresis (SDS‐PAGE) analysis and enzyme activity determination. Unfrozen and frozen fish and shellfish meats were heat‐treated at different selected temperatures with 0, 15 or 30 min holding times. Proteins were extracted with NaCl solution. The coagulation method was able to determine EPT of heated fish and shellfish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…2) may be also explained by protein aggregation due to heat denaturation. As for shrimp tropomyosin, Uddin et al (2002) reported that tropomyosin from kuruma prawn (Penaeus japonicus) was highly thermostable and resistant to heatinduced aggregation up to 108℃, even in the presence of other proteins. Despite differences in shrimp species, the resistance to heat-induced aggregation might be similar for pink shrimp tropomyosin because of the high amino acid sequence identity (96.8%) between kuruma prawn and pink shrimp (Motoyama et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…2) may be also explained by protein aggregation due to heat denaturation. As for shrimp tropomyosin, Uddin et al (2002) reported that tropomyosin from kuruma prawn (Penaeus japonicus) was highly thermostable and resistant to heatinduced aggregation up to 108℃, even in the presence of other proteins. Despite differences in shrimp species, the resistance to heat-induced aggregation might be similar for pink shrimp tropomyosin because of the high amino acid sequence identity (96.8%) between kuruma prawn and pink shrimp (Motoyama et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no reason for excluding heating processes from the research schedule. A Japanese research group worked for 6 years on methods for determining the end‐point temperature (EPT) of fish and shellfish meats (Uddin et al. 2000; 2002a,b; 2005).…”
Section: Introductionmentioning
confidence: 99%
“…EPT of cooked meat and meat products has been determined using different methods including determination of enzyme activity, coagulation test and Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis (SDS-PAGE) (Uddin, Ishizaki, Ishida, & Tanaka, 2002;Wang, Abouzied, & Smith, 1996). However, common to these techniques are that they are time consuming, destructive and labour intensive.…”
Section: Introductionmentioning
confidence: 99%